HUBUNGAN ASUPAN PROTEIN, OMEGA 3, OMEGA 6 DAN ZINK TERHADAP TUMBUH KEMBANG BALITA - Pijaryani, Indria (Politeknik Kesehatan Kemenkes Bengkulu, 2014)
The growth and development is an evolutionary process that includes the stages of change through a physical , cognitive , and emotional that can be identified . From the initial survey conducted by the researchers found two toddler nutrition toddler skinny and one fat nutritional status with the percentage ( 50 % ) are not age-appropriate development . This study used a cross sectional. Seen from the growth and nutritional status of pre- screening questionnaire development (KPSP). The sample amounted to 96 toddlers . Proportional sampling technique using random sampling . Data was collected through primary and secondary data . Data processed Chi-square test and multiple logistic regression . The results of both studies of protein intake with corresponding growth as much as 94.3 % , statistical tests showed no correlation with p value of 0.00 . Intake of omega- 3 well with normal growth and development as much as 96.2 % , statistical tests showed no p value of 0.008 . Intake of omega- 6 well with normal growth and development as much as 95 % , statistical tests showed no correlation with p value of 0.042. Zinc intake well with the corresponding growth as much as 95.7 % , statistical tests showed no correlation with p value 0.019 . Results of multiple logistic regression known intake of omega 3 are factors that influence the growth and development of the value ekponen is 9.209 , so the omega- 3 chance 9.2 times affect the growth and development of infants.